Key Production Parameters to Obtain Transparent Nanocellular PMMA. Issue 12 (17th October 2017) - Martín‐de León, Judith; Bernardo, Victoria; Rodríguez‐Pérez, Miguel Ángel
Abstract: Transparent nanocellular polymethylmethacrylate (PMMA) with relative density around 0.4 is produced for the first time by using the gas dissolution foaming technique. The processing conditions and the typical characteristics of the cellular structure needed to manufacture this novel material are discovered. It is proved that low saturation temperatures (−32 °C) combined with high saturation pressures (6, 10, 20 MPa) allow increasing the solubility of PMMA up to values not reached before. In particular, the highest CO2 uptake ever reported for PMMA, (i.e., 48 wt%) is found for a saturation pressure of 20 MPa and a saturation temperature of −32 °C. Due to these processing conditions, cell nucleation densities of 10 16 nuclei cm −3 and cell sizes clearly below 50 nm are achieved. The nanocellular polymers obtained, with cell sizes ten times smaller than the wavelength of visible light and very homogeneous cellular structures, show a significant transparency. Abstract : Transparent nanocellular polymethylmethacrylate (PMMA) is produced for the first time. The key parameters needed for its production are low saturation temperatures (−32 °C) combined with high saturation pressures (6–20 MPa). The materials obtained by using this method present high homogeneous cellular structure, with cell nucleation densities higher than 10 16 nuclei cm −3 and cell sizes clearly below 50 nm.